Partnering With Patients in a Quality Improvement Curriculum for Internal Medicine Residents - Wahlberg, Kramer J (J Patient Exp, 2021)
Patient experience is a core component of the Institute for Healthcare Improvement Triple Aim for health care improvement. Although resident physicians must meet quality improvement (QI) competencies prior to graduation, QI training during residency may not adequately prepare residents to improve patient and family experience. We describe an active learning QI curriculum engaging 3 Patient and Family Advisors as partners alongside 15 resident physicians. This partnership proved to be a meaningful experience for both groups, with the development of mutual respect and insight into the contributions that patients and families bring to solving problems in health care quality.